2018
DOI: 10.1017/ipo.2017.29
|View full text |Cite
|
Sign up to set email alerts
|

Was Mattarella worth the trouble? Explaining the failure of the 2016 Italian constitutional referendum

Abstract: The election of President Mattarella is a turning point in Matteo Renzi’s attempt to reform the constitution. This choice determined the loss of Forza Italia’s support to the constitutional reform, thus leaving the Renzi cabinet and the Democratic Party alone on the Yes-side. Our goal is to assess the degree of Renzi’s misjudgment by comparing two theoretical perspectives on voting behavior in direct-democratic settings through a nested design. Our results highlight that vote choices can be explained by both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Economic crises can be very relevant. The state of the economy is generally deemed as a proxy for the performance of the cabinet, so that if the economic situation worsens, citizens will punish the incumbent (Negri & Rebessi, 2018). Accordingly, when the economic situation is negative, presidents can expect that public opinion will support their viewpoint (Grimaldi, 2023) and will turn against the prime minister, in case of a conflict over the promulgation of laws.…”
Section: Hypothesis 3 (H3)mentioning
confidence: 99%
See 1 more Smart Citation
“…Economic crises can be very relevant. The state of the economy is generally deemed as a proxy for the performance of the cabinet, so that if the economic situation worsens, citizens will punish the incumbent (Negri & Rebessi, 2018). Accordingly, when the economic situation is negative, presidents can expect that public opinion will support their viewpoint (Grimaldi, 2023) and will turn against the prime minister, in case of a conflict over the promulgation of laws.…”
Section: Hypothesis 3 (H3)mentioning
confidence: 99%
“…Economic crises can be very relevant. The state of the economy is generally deemed as a proxy for the performance of the cabinet, so that if the economic situation worsens, citizens will punish the incumbent (Negri & Rebessi, 2018). Accordingly, when the economic situation is negative, presidents can expect that public opinion will support their viewpoint (Grimaldi, 2023) and will turn against the prime minister, in case of a conflict over the promulgation of laws.Hypothesis (H4): The number of laws rejected by the president will increase in times of economic crises, when the state of the economy worsens.Hypothesis (H5): The number of laws rejected by the president will increase in times of institutional crises.…”
Section: Hypothesesmentioning
confidence: 99%
“…In the context of topdown national referenda, and especially when the issues at stake are complex, it has been shown that partisanship might represent a powerful cue, allowing people to vote without having to understand every detail of the issue at stake, by merely aligning to the decision suggested by the party they support and trust in (Hobolt, 2007;Quaranta et al, 2019). After 2016 Italian constitutional referendum various studies showed that the vast majority of voters aligned to the decision of the parties they supported (Di Mauro and Memoli, 2018;Negri and Rebessi, 2018).…”
Section: Introductionmentioning
confidence: 99%